Big Five personality traits, dispositional affect, and financial satisfaction among older adults. (1st November 2020) - Tharp, Derek T.; Seay, Martin C.; Carswell, Andrew T.; MacDonald, Maurice
Abstract: While previous studies have found that personality is one of the strongest predictors of life satisfaction, the associations between personality and financial satisfaction have not been assessed using large, nationally representative datasets. This study investigates relationships between personality (Big Five personality traits and dispositional positive/negative affect) and financial satisfaction using data from the 2012 wave of the Health and Retirement Study (HRS). Results from a three-block ordinal logistic regression model ( n  = 3984) indicate that personality traits are important predictors of financial satisfaction. When incorporating Big Five personality traits into a leading model of financial satisfaction, extraversion was positively associated with financial satisfaction, while neuroticism and agreeableness were negatively associated with financial satisfaction. However, when positive affect and negative affect were added to the model including Big Five traits, only agreeableness and negative affect were found to be negatively associated with financial satisfaction, while positive affect was positively associated with financial satisfaction. Additionally, this study examined the convergent validity, test-retest reliability, and presence of common method bias among the Big Five and dispositional affect measures used within the HRS, finding that the measures are reasonable for use in personality research. Highlights: Personality is an important predictor of financial satisfaction. Extraversion is positively associated with financial satisfaction. Neuroticism and agreeableness negatively associated with financial satisfaction. Positive and negative affect are stronger predictors than Big Five traits. Positive affect (+) and negative affect (−) predict financial satisfaction.